2011
DOI: 10.1097/mlr.0b013e318215d5e2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Johns Hopkins Aggregated Diagnosis Groups (ADGs) to Predict Mortality in a General Adult Population Cohort in Ontario, Canada

Abstract: Background-Administrative health care databases are increasingly used for health services and comparative effectiveness research. When comparing outcomes between different treatments, interventions or exposures, the ability to adjust for differences in the risk of the outcome occurring between treatment groups is important. Similarly, when conducting health care provider profiling, adequate risk-adjustment is necessary for conclusions about provider performance to be valid. There are limited validated methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
271
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 321 publications
(273 citation statements)
references
References 17 publications
1
271
0
1
Order By: Relevance
“…These variables included age, income quintile, rural residence, prior breast screening, index mammogram result, breast cancer family history, primary care physician (PCP) visits, the number of Johns Hopkins major aggregate diagnosis groups (ADGs),21 duration of residence in Canada, immigration class and application type, as well as Canadian language proficiency and education level at the time of landing. The full definitions of these variables can be found in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…These variables included age, income quintile, rural residence, prior breast screening, index mammogram result, breast cancer family history, primary care physician (PCP) visits, the number of Johns Hopkins major aggregate diagnosis groups (ADGs),21 duration of residence in Canada, immigration class and application type, as well as Canadian language proficiency and education level at the time of landing. The full definitions of these variables can be found in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…For each man who underwent vasectomy, we selected one man who did not, matching on age (within two years), comorbidity score (defined using the Johns Hopkins adjusted clinical groups case mix system),47 geographical area (defined by the first three digits of the postal code), and index date. The Johns Hopkins adjusted clinical case mix system was designed to predict healthcare use and considers the duration, severity, and intensity of service use related to both inpatient and outpatient claims, details of which have been provided elsewhere 48.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, ADGs were analyzed using a previously validated scoring system utilizing weighted ADG scores and collapsing age and gender (Mortality Risk Score). 115 The Johns Hopkins ACG system has been well established as a tool to predict health care resource utilization, but more recent studies have also demonstrated its ability to predict mortality and long-term hospitalization. 116 Furthermore, ADGs accurately predict 1-year mortality in the general population and performed well compared to other established methods of comorbidity adjustment (Charlson comorbidity score).…”
Section: Johns Hopkins Adjusted Clinical Groups Systemmentioning
confidence: 99%
“…116 Furthermore, ADGs accurately predict 1-year mortality in the general population and performed well compared to other established methods of comorbidity adjustment (Charlson comorbidity score). 117 The…”
Section: Johns Hopkins Adjusted Clinical Groups Systemmentioning
confidence: 99%